Vermifiltration Of Palm Oil Mill Effluent - Malek, Tengku Erina Ungku Abdul (2014)
The performance of vermifiltration (VF) systems using the Lumbricus rubellus and Eudrillus eugeniae earthworm in treating palm oil mill effluents (POME) was studied. In this work, POME is an organic wastewater generated from the production of crude palm oil that is high in COD, BOD, TSS concentration, low in pH, oily and has unpleasant odor and is difficult to treat and to comply with the environmental standard. POME was treated through this system, after which the changes in pH, COD and TSS were recorded. In vermifiltration system, both earthworms’ species, Eudrilus eugeniae and Lumbricus rubellus can be used to treat wastewater. They could remove TSS and COD concentrations in the range of 80%- 97%. The addition of vermicast filter could also increase the percentage of TSS reduction from 88% to 97% and percentage of COD reduction from 84% to 95%. The presence of plant showed no effect on water quality of treated POME in vermifilter with plant and without plant. This study has showed that the presence of earthworms could aid in increasing the removal efficiency of TSS and COD. TSS reduction in vermifilter was 95% which is higher than control filter, 87%. Meanwhile, for COD reduction, vermifilterremoved 91% of COD concentration and control filter removed only 82%. Based on this study also, it was found that for vermifiltration system, the most suitable hydraulic loading rate and worm density to be used in vermifiltration of POME where the efficiency of treatment was more than 90% were at 940 mL/min m2 and 8 g/L respectively.